2006
DOI: 10.1055/s-2006-955466
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Acute Pulmonary Embolism

Abstract: Acute pulmonary embolism (PE) is a potentially life-threatening condition, with an overall 3-month mortality rate of 15% and with right ventricular failure as the most common cause of early death. Risk stratification facilitates identification of high-risk patients and may be helpful in guiding the initial and long-term management. In patients with massive PE and hemodynamic instability, rapid risk assessment is paramount and bedside echocardiography and multislice chest computed tomography (CT) are useful for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 63 publications
0
38
0
7
Order By: Relevance
“…The significance of our study is its proposal of an additional parameter that reflects modifications in cardiac morphology in response to pulmonary arterial obstruction in patients with acute PE. Atrial assessment is rapid and easy and may therefore contribute to the establishment of CTPA as a useful tool for both the diagnosis of PE and the identification of those patients with cardiac morphological changes that are associated with a high embolic load who might be at risk of sudden circulatory collapse and, consequently, may be considered for closer monitoring, with possible thrombolytic therapy [3]. Pathophysiological studies have suggested that there is an increase in pulmonary vascular resistance due to the anatomical obstruction caused by the emboli, release of vasoconstricting agents and reflex hypoxemia during a major PE event [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of our study is its proposal of an additional parameter that reflects modifications in cardiac morphology in response to pulmonary arterial obstruction in patients with acute PE. Atrial assessment is rapid and easy and may therefore contribute to the establishment of CTPA as a useful tool for both the diagnosis of PE and the identification of those patients with cardiac morphological changes that are associated with a high embolic load who might be at risk of sudden circulatory collapse and, consequently, may be considered for closer monitoring, with possible thrombolytic therapy [3]. Pathophysiological studies have suggested that there is an increase in pulmonary vascular resistance due to the anatomical obstruction caused by the emboli, release of vasoconstricting agents and reflex hypoxemia during a major PE event [18].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the evaluation of patients with suspected PE consists of echocardiography and CTPA [3]. Echocardiography is both a rapid and accurate risk-assessment tool that is useful in identifying the PE patients who have a poor prognosis [3,21,22]. Its ability to visualize pulmonary arterial clots that are not very large or centrally located is, however, quite limited [21].…”
Section: Discussionmentioning
confidence: 99%
“…RV enlargement, defined by the ratio of RV to LV size of more than 1 in an apical 4 chamber view without obvious causes in the setting of pulmonary hypertension, was also considered as RV dysfunction in the present study. 16, 39 To quantify the degree of RV dysfunction, fractional area change (FAC) and tricuspid annular plane systolic excursion (TAPSE) was measured according to the current guidelines.…”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…Transthoracic echocardiography that was ordered within the first 24 hours was examined with a Philips Envisor C model echocardiography device and 3.2 mHz adult probe. On transthoracic evaluation, right ventricular dysfunction was accepted as tricuspid regurgitation jet velocity >2.6 m/sec, hypokinesis, or dilation in the right ventricular wall (right ventricular end-diastolic diameter/left ventricular end-diastolic diameter >1 in apical four-chamber) (4,17).…”
Section: Methodsmentioning
confidence: 99%